Detecting unfrozen sediments below thermokarst lakes with surface nuclear magnetic resonance. Issue 3 (11th February 2013) - Parsekian, Andrew D.; Grosse, Guido; Walbrecker, Jan O.; Müller‐Petke, Mike; Keating, Kristina; Liu, Lin; Jones, Benjamin M.; Knight, Rosemary
Abstract [1] A talik is a layer or body of unfrozen ground that occurs in permafrost due to an anomaly in thermal, hydrological, or hydrochemical conditions. Information about talik geometry is important for understanding regional surface water and groundwater interactions as well as sublacustrine methane production in thermokarst lakes. Due to the direct measurement of unfrozen water content, surface nuclear magnetic resonance (NMR) is a promising geophysical method for noninvasively estimating talik dimensions. We made surface NMR measurements on thermokarst lakes and terrestrial permafrost near Fairbanks, Alaska, and confirmed our results using limited direct measurements. At an 8 m deep lake, we observed thaw bulb at least 22 m below the surface; at a 1.4 m deep lake, we detected a talik extending between 5 and 6 m below the surface. Our study demonstrates the value that surface NMR may have in the cryosphere for studies of thermokarst lake hydrology and their related role in the carbon cycle.